(3eONd Gdi GdJNWjWs - (3ehSj jhSa(B, (3NejSs ((3YeGf(B:s (3OGQ GdTQhb ddfTQ hGdJhRjY(B,s, 1999)
(3eONd Gdi GdJNWjW(B- (3CHYGO hechfGJ hNUGFU GdJNWjW(B- (3eQGMd GdYedjI GdJNWjWjI(B- (3GdeQcRjI hGddGeQcRjI aj GdJNWjW(B- (3GdeTGQcI GdTYHjI aj GdJNWjW(B- (3GdJNWjW aj GdGQOf(B- (3feGPL JNWjWjI(B.s
Keywords: (3GdEOGQIs; (3GdJNWjWs